Securing future water supply for Iran through 100% renewable energy powered desalination - Caldera, Upeksha; Bogdanov, Dmitrii; Fasihi, Mahdi; Aghahosseini, Arman; Breyer, Christian (International Journal of Sustainable Energy Planning and Management, 2019)
Iran is the 17th most populated country in the world with several regions facing high or extremely high water stress. It is estimated that half the population live in regions with 30% of Iran’s freshwater resources. The combination of climate change, increasing water demand and mismanagement of water resources is forecasted to worsen the situation. This paper shows how the future water demand of Iran can be secured through seawater reverse osmosis (SWRO) desalination plants powered by 100% renewable energy systems (RES), at a cost level competitive with that of current SWRO plants powered by fossil plants in Iran. The optimal hybrid RES for Iran is found to be a combination of solar photovoltaics (PV) fixed-tilted, PV single-axis tracking, Wind, Battery and Power-to-Gas (PtG) plants. The levelised cost of water (LCOW) is found to lie between 1.0 €/m3 – 3.5 €/m3, depending on renewable resource availability and water transportation costs.